From selection to scale: Understanding early-stage soil health innovations in Africa - Hauke, Dahl; Peterson, Nathanial Richard (2025)
Soil degradation remains a major constraint to agricultural productivity and climate resilience across Sub-Saharan Africa. In recent years, private enterprises have begun to play a growing role in developing and commercializing technologies that address soil fertility, diagnostics, and regenerative practices. This report, From Selection to Scale: Understanding Early-Stage Soil Health Innovations in Africa, provides an overview of emerging private-sector models that complement public research and development efforts. Using a sample of early-stage ventures operating in soil testing, bio-inputs, precision agriculture, and carbon sequestration, the report examines their technologies, business approaches, and implementation contexts. It identifies common patterns in market entry, financing, and impact pathways, as well as constraints related to data access, regulation, and technical validation. The analysis proposes a set of indicators for tracking soil-health innovation outcomes and outlines areas where coordinated investment and policy support could enhance the scalability and effectiveness of private-sector engagement in sustainable soil management.